BIOCHEMICAL ESTIMATION OF WILD GANODERMA LUCIDUM COLLECTED FROM DIFFERENT AGRO-CLIMATIC ZONES OF HARYANA - SONIA TAKSHAK; REETI CHAUDHARY; ANIL SINDHU; AJAY SINGH (International Journal of Pharma and Bio Sciences, 2014)
Ganoderma lucidum, commonly known as Rieshi or Lingzhi is a white-rot fungus of division basidiomycetes. G. lucidum is an important species from economical and medicinal point of view. Wild G. lucidum samples collected from four agro-climatic zones of Haryana state were oven-dried and analyzed for proximate, mineral and antinutrient compositions. The samples contained moisture content in the range of 75-80%, ash content (4-10%), crude fiber (20-38%), crude fat (3-5%), crude protein (18-22%) and carbohydrates (28-54%). Total soluble sugars were comparable within the range of 10.5-11.5%. No available calcium was found to be present whereas total iron and total zinc were present in the range of 3-6 ppm and 0.9-2 ppm respectively. Anti-nutrients, phytic acid and oxalic acid were found on the lower side in the range 1.7-3% and 0.50.9% respectively. The presence of these essential nutrients revealed the potential of G. lucidum to be used as a good diet supplement